Severe Chagas disease in Ecuador: a countrywide geodemographic epidemiological analysis from 2011 to 2021 - Vásconez-González, Jorge; Izquierdo-Condoy, Juan S.; Fernandez-Naranjo, Raul; Gamez-Rivera, Esteban; Tello-De-la-Torre, Andrea; Guerrero-Castillo, Galo S.; Ruiz-Sosa, Carlos; Ortiz-Prado, Esteban (Frontiers in Public Health, 2023)
Abstract Background: Chagas disease is a neglected and often forgotten tropical disease caused by the Trypanosoma cruzi. This parasite can be transmitted through the direct contact of human skin with feces and urine of the triatomine insect. According to the World Health Organization (WHO), an estimated 6–7 million people are infected worldwide, killing at least 14,000 every year, being Africa and South America the most affected regions. Methodology: We analyzed the morbidity and mortality rates of severe Chagas disease in Ecuador on a nationwide, population-based level. Hospitalization cases and deaths were also examined based on altitude, including low (<2,500 m) and high (>2,500 m) altitudes, and the International Society of Mountain Medicine altitude classification. Data was retrieved from the National Institute of Statistics and Census hospital admissions and in-hospital mortality databases from 2011-2021. Results: A total of 118 patients have been hospitalized in Ecuador since 2011 due to Chagas disease. The overall in-hospital mortality rate was 69.4% (N = 82). Men have a higher incidence rate (4.8 / 1’000,000) than women, although women have a significantly higher mortality rate than men (6.9 / 1’000.000). Conclusion: Chagas disease is a severe parasitic condition that primarily affects rural and poorer areas of Ecuador. Men are more likely to be infected due to differences in work and sociocultural activities. Using average elevation data, we conducted a geodemographic analysis to assess incidence rates by altitude. Our findings indicate that the disease is more common at low and moderate altitudes, but recent increases in cases at higher altitudes suggest that environmental changes, such as global warming, could be driving the proliferation of disease-carrying vectors in previously unaffected areas.